PO 5 - HORNER SYNDROME IN A PARTURIENT AFTER COMBINED SPINAL/EPIDURAL ANESTHESIA - Nuno Alçada1,; Paulo Correia1,; Caroline Dahlem1,; Marcos Pacheco1, (Journal of the Portuguese Society of Anesthesiology, 2023)
.